2015
DOI: 10.1016/j.nano.2014.12.019
|View full text |Cite
|
Sign up to set email alerts
|

An in silico analysis of nanoparticle/cell diffusive transfer: Application to nano-artificial antigen-presenting cell:T-cell interaction

Abstract: Polymeric nanoparticles (nano-paAPCs) modified with T-cell antigens and encapsulating immunostimulatory or immunoinhibitory factors may act as artificial antigen-presenting cells to circulating immune cells, improving the selective delivery of encapsulated drug or cytokine to antigen-specific T-cells. Paracrine delivery of encapsulated agents from these nanoparticles to adjacent cells facilitate sustained delivery lowering the overall administered dose, thus enhancing the overall drug efficacy while reducing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…In previous studies, Fahmy and Laboswky, described an in silico model demonstrating how the nature and profile of this concentration gradient near a cell surface or embedded in a cell develops over time and space. Specifically, it was shown that an encapsulated drug can accumulate to several orders of magnitude above systemic free doses within the target of interest and dependent on the proximity of the nanoparticle to the target (14). Such a targeted delivery system, if used in humans, could significantly curtail the side effect profile associated with these drugs and improve patient quality of life, in addition to increasing efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, Fahmy and Laboswky, described an in silico model demonstrating how the nature and profile of this concentration gradient near a cell surface or embedded in a cell develops over time and space. Specifically, it was shown that an encapsulated drug can accumulate to several orders of magnitude above systemic free doses within the target of interest and dependent on the proximity of the nanoparticle to the target (14). Such a targeted delivery system, if used in humans, could significantly curtail the side effect profile associated with these drugs and improve patient quality of life, in addition to increasing efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…We previously modeled mathematically the “flattening” of the cell interface as it interacts with the particle, identifying a significantly enhanced magnitude of cytokine accumulation at the cell–particle interface . This phenomenon of “paracrine effect post release” suggests that targeting, and therefore ligation, via anti‐CD2 and anti‐CD4 antibodies could bring particles and T cells within nanoscale ligand–receptor distances, increasing the local concentration of cytokines available to cells with great efficacy .…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon of “paracrine effect post release” suggests that targeting, and therefore ligation, via anti‐CD2 and anti‐CD4 antibodies could bring particles and T cells within nanoscale ligand–receptor distances, increasing the local concentration of cytokines available to cells with great efficacy . This phenomenon occurs in systems of artificial antigen presentation, where IL‐2 encapsulated in NPs has an equivalent T cell stimulatory effect to soluble IL‐2 at a 1,000‐fold higher concentration . NPs also create a local acidic microenvironment that can convert endogenous latent TGFβ to its active form, and this could synergize with IL‐2 in extending Treg cell expansion—even after the TGFβ stores in the NPs are depleted.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work, Labowsky et al . described an in silico model demonstrating how the nature and profile of this concentration gradient near a cell surface develops over time and space, although the upper limit of drug delivery is not known27. Covalent linkage of the NP allows delivery of therapeutic agents directly into the circulatory system with minimal shedding of the NP into the systemic circulation and most organs, although some NP can be found in the liver, kidney and spleen.…”
Section: Discussionmentioning
confidence: 99%